2014
DOI: 10.4209/aaqr.2013.03.0071
|View full text |Cite
|
Sign up to set email alerts
|

Composition of PM2.5 and PM10 Collected at Urban Sites in Brazil

Abstract: Atmospheric particulate matter samples (PM 2.5 and PM 10 ) were collected at urban sites (São Paulo, SPA; Piracicaba, PRB) in São Paulo State, Brazil. In order to characterize the chemical composition of particulate matter, several chemical components were analyzed from the samples, and among these were inorganic and organic anions, monosaccharide anhydrides, and organic and elemental carbon. Long-range transport of the particulate matter while sugar cane was being burned contributed to an increase in PM 2.5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
3
19

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 36 publications
(41 reference statements)
8
27
3
19
Order By: Relevance
“…In this study it was found that, on average, more than 60 % of the total mass PM is within the category PM 2.5 ; it is consistent with a previous study performed at this site (dry season, 2008) when this value was 69 % (Souza et al, 2014a). Conversely, in a 2-year study conducted at 10 urban sites in Rio de Janeiro, the coarse fraction represented from 60 to 70 % of the PM 10 mass concentration (Godoy et al, 2009).…”
Section: Statistical Analysis and Receptor Modelsupporting
confidence: 80%
See 2 more Smart Citations
“…In this study it was found that, on average, more than 60 % of the total mass PM is within the category PM 2.5 ; it is consistent with a previous study performed at this site (dry season, 2008) when this value was 69 % (Souza et al, 2014a). Conversely, in a 2-year study conducted at 10 urban sites in Rio de Janeiro, the coarse fraction represented from 60 to 70 % of the PM 10 mass concentration (Godoy et al, 2009).…”
Section: Statistical Analysis and Receptor Modelsupporting
confidence: 80%
“…The average temperatures ranged from 15 to 21 • C and the wind speed ranged between 0.6 and 2.2 km h −1 . The concentrations of PM 2.5 in the intensive campaign ranged from 15 to 88 µg m −3 (average 45 µg m −3 ), with a similar average to that obtained in another intensive study in 2008, 47 µg m −3 (Souza et al, 2014a). The levels of PM 2.5 in this campaign were above the levels recommended by WHO on 90 % of the sampling days.…”
Section: Concentrations Of Pm 25 During the Intensive Campaignsupporting
confidence: 53%
See 1 more Smart Citation
“…Burning of sugarcane residue during the May-October period has clear effects on local air quality by affecting PM chemical composition in the MASP (Allen et al, 2009;Souza et al, 2014;Vasconcellos et al, 2010). During the burning period, air masses from the areas of biomass burning circulate over the sea and over the biggest industrial park in the state (Cubatão, a city with chemical, pharmaceutical, petrochemical, steel and fertiliser manufacturing, among other activities) prior to reaching the MASP (Vasconcellos et al, 2010).…”
Section: Influence Of Other Local and External Sourcesmentioning
confidence: 99%
“…On the other hand, comprehensive structural identification within the complex aerosol WSOC mixture has been rarely reported for Southern Hemisphere locations. Most field studies within this region have included measurements of ambient concentrations of OC, elemental carbon (EC), and WSOC, specific organic markers (e.g., n-alkanes, PAHs, and levoglucosan), or the amount of hydrocarbon-like and oxygenated OA components [e.g., in Brisbane (Australia), Tanzania (rural background site), São Paulo (Brazil), Rondônia (Amazon Basin, Brazil), Buenos Aires (Argentina), Bogota (Colombia), and Santiago (Chile)] Mayol-Bracero et al, 2002;Tagliavini et al, 2006;Vasconcellos et al, 2010Vasconcellos et al, , 2011Mkoma and Kawamura, 2013;Crilley et al, 2014;Souza et al, 2014;De Oliveira Alves et al, 2015;Villalobos et al, 2015). Although these studies have provided a glimpse into the bulk chemical makeup of OA, the current understanding of the role of aerosol WSOC in global climate change still is incomplete.…”
Section: Introductionmentioning
confidence: 99%